Increasing Commitment To The Profession Through Strengthening Organizational Culture, Self-Efficacy, Job Satisfaction, And Work Motivation - Adi Permana; Bibin Rubini; Sumaryoto Sumaryoto (Journal of Social Research, 2024)
Teachers as one of the components of education play an important role in teaching and learning activities. In the general provisions of Law No. 14 of 2005 concerning teachers and lecturers, it is stated that teachers are professional educators with the main task of educating, teaching, guiding, directing, assessing and evaluating students at various levels and types of formal education. This research aims to find strategies and ways to increase commitment to the profession. This study uses a quantitative approach, namely research that emphasizes its analysis on numerical data (numbers) processed by statistical methods. The first hypothesis states that Self-Efficacy has a direct positive and significant effect on Commitment to the Profession. Based on the results of research and data processing, it can be concluded that commitment to the profession can be increased through Strengthening Organizational Culture, Self-Efficacy, Job Satisfaction, and Work Motivation.